Penguatan Nilai-Nilai Agama Terhadap Masyarakat Desa Dahian Tunggal Dalam Mencegah Terjadinya Perceraian : (Studi Agama Islam, Kristen, Dan Hindu Kaharingan) - Alfianoor Alfianoor; Rio Ariza; Siti Aisah; Laura Qeeren Hacpukh; Kasandra Pranika; Nacha Enjelika; Radea Delateka Sorongan; Rollan Christiano; Suriantie Suriantie; Pina Pina; Afrianto Rehiara; Titinian Situmeang (BADAN PENERBIT STIEPARI PRESS, 2023)
Divorce in Islam is called talak, which is the termination of a husband and wife relationship from a legal marriage relationship according to the rules of the Islamic religion and the state, in Islam divorce is considered something that is permissible but is not liked by Allah. Meanwhile, divorce in Christianity is considered a deviation from God's teachings, which is not permissible at all until death do them part. In Hinduism, divorce is highly avoided, because it is an act of Adharma or sin. Divorce is a problem that is prone to occur in Dahian Tunggal village. Strengthening religious values is a solution in tackling the increase in divorce. Because every religion views divorce as something that is strictly prevented, and marriage is something that must be kept intact. This research is a field study research and collects the results of interviews with religious leaders, the community, village officials, and so on which are used as research material evidence. This research uses the ABCD method and field types